Evidence that grey seals (Halichoerus grypus) use above-water vision to locate baited buoys - Fjälling, Arne; Keiner, Jenny; Beszczyńska, Magdalena (NAMMCO Scientific Publications, 2007)
Fishing gear in the Baltic is often raided by grey seals (Halichoerus grypus). The seals remove the fish and damage the nets, or entangle themselves and drown. In order to develop ways of mitigating the seals-fisheries conflict, it is important to know exactly how the seals locate the fishing gear. A field experiment was conducted in order to clarify whether seals use their vision above water to do this. Bait (herring; Clupea harengus) was attached to the anchor lines of buoys of the type that is commonly used to mark the position of fishing gear. In all, 643 buoys were set. Some of the buoys (210) were also fitted with camera traps. Weather data were collected from official weather stations nearby. Bait loss (mean 18%) was significantly correlated with buoy size (P = 0.002) and wind speed (P = 0.04). There was a significant association between bait loss and seal observations near the buoys (P = 0.05). Five photos of grey seals were obtained from the camera traps. No fish-eating birds, such as cormorants or mergansers, were ever observed near the buoys or caught on camera. It was concluded that a main cause of missing bait was scavenging by grey seals, and that they did use above-water vision to locate the buoys. It was also concluded that wind strength (i.e. wave action) contributed tothe bait loss. The camera trap buoys had a somewhat lower bait loss than the other buoys (P = 0.054), which was attributed to a scaring effect. Neither the number of seal observations nor the bait loss differed significantly between the 2 study areas in the experiment (P = 0.43 and P = 0.83, respectively). Bait loss was not affected by the buoy colour (red, white, or grey; P = 0.87). We suggest that the findings of this experiment could be put into practice in a seal-disturbed area by deploying a number of decoy buoys, or by hiding live buoys below the surface of the water. This would increase the cost of foraging for the seals, and hence discourage them from exploiting fishing gear as a feeding place.